Best Answer

x3 + 2x2 - 35x

= x(x2 + 2x - 35)

= x(x + 7)(x - 5)

More answers

Assuming that's -35, that factors to (2x + 5)(4x - 7)

(x - 7)(x + 5)

(7x + 5)(2x - 7)

(3x - 7)(4x + 5)

x(x + 5)(x - 9)

x(x - 7)(x + 5)

Q: What is the factorization of x3 plus 2x2-35x?

Write your answer...

Submit

Still have questions?

Continue Learning about Movies & Television

(X minus the cube root of fifteen) times (x squared plus the cube root of fifteen plus fifteen to the two thirds power)

(x + 4)(x + 1)

8m(4 + 7p)

4v4 + 16v3 = 4v3 (v + 4)

-x(x2 - 2)(x2 + 3)

Related questions

x3 + 13x2 + 42x = x(x + 6)(x + 7).

x3 + 2x2 - 35x = x(x + 7)(x - 5)

It is: (x2 + 5x) (x + 8)

x(x + 8)(x + 5)

x(x + 9)(x + 5)

x3 - 7x2 + 6x =x (x2 - 7x + 6) =x (x - 6) (x - 1)

x3 - 12x2 + 35x = x (x2 - 12x + 35) = x (x - 7) (x - 5)

34 · m2 · x3

2x3 - 7 + 5x - x3 + 3x - x3 = 8x - 7

7 x 3 x3

x3 + 13x2 + 42x = x(x2 + 13x + 42) = x(x2 + 6x + 7x + 42) = x[x(x + 6) + 7(x + 6)] = x(x + 7)(x + 6)

X3 + 13X2 + 40X factor out an X X(X2 + 13X + 40) factor the quadratic expression, what two factors of 40 add up to 13? X(X + 8)(X + 5) works the same if that is a negative in front of X3, just sign changes